Single-visit apexification with Biodentine and platelet-rich fibrin - Nitin Khanduri; Deepak Kurup (Wolters Kluwer Medknow Publications, 2018)
Apexification is the process of induction of calcific barrier across the open apex or the continued apical development in an immature tooth with infected necrotic pulp. The presented case was of a 19-year-old male patient with discolored and fractured upper front left tooth and open apex. Immature permanent teeth pose difficulties during endodontic treatment because of the wide-open root apex and thin dentin walls. This article describes single-visit apexification using Biodentine, a new calcium silicate-based material as an apical barrier along with platelet-rich fibrin as internal matrix.